Dust and smoke : air pollution and colonial urbanism, India, c.1860-c.1940 - Sharan, Awadhendra B. (Hyderabad, Telangana, India : Orient BlackSwan, 2020)
With a special reference to Kolkata and Mumbai, India.
Includes bibliographical references (pages 287-303) and index.
Keywords: Air -- Pollution -- India -- Kolkata; Air -- Pollution -- India -- Mumbai; Urbanization -- Environmental aspects -- India -- Kolkata; Urbanization -- Environmental aspects -- India -- Mumbai; Air -- Pollution -- Government policy -- India -- Kolkata; Air -- Pollution -- Government policy -- India -- Mumbai; Environmental law -- India -- Kolkata; Environmental law -- India -- Mumbai; Air -- Pollution; Air -- Pollution -- Government policy; Environmental law; Urbanization -- Environmental aspects; India -- Kolkata; India -- Mumbai